Models of Assignment on Endocrine and Reproduction Block (1.5), Faculty of Medicine, Islamic University of Indonesia (FM IUI) - Alin Julda Qonita; Syaefudin ali Akhmad (Faculty of Medicine, Universitas Islam Indonesia, 2015)
Background: Doctor’s competency in Indonesia covers seven pillars namely noble professionalism and ethics, self-development and selfcontrol, effective communication, information management, scientificfoundation of medicine, clinical skills, and problem management on public health. One of the efforts to achieve the competency especially on ethics, self development and information management competency, FM IUI has used assignment model in Block of 1.5.Objective: The study was conducted to describe the models of assignment to increase the ability of writing skill citation and bibliography using Mendeley, to avoid plagiarism using VIPER and to access journal using Clinical Key.Methods: This descriptive study focused on all students following Block 1.5 which consists of 45 male students and 95 female students. The research instrument was questionnaire for collecting data from all respondents after assignment finished.Results: Three models of assignment is used to increase the ability in writing using Mendeley, to avoid plagiarism using VIPER and to increase in accessing electronic journal (ClinicalKey). First week on Block of 1.5 was to introduce the assignment and practical work using CinicalKey, Mendeley and VIPER. The comparison between before and after assignment to use Mendeley, VIPER and ClinicalKey analyzed from questionnaire.Conclusion: The percentage of students in using Mendeley, ClinicalKey and VIPER has increased up to 90 %.